AN ECONOMICAL STUDY TO MEASUREMENT OF MARKETING EFFICIENCY IN CALF FATTENING FIELDS IN NINEVEH GOVERNORATE(2018) - & Al-Taye, Abdullah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed at assessing marketing efficiency in the main sites of meat production of calf fattening fields in the private sector due to the importance of meat, especially red meat, which has essential nutrient for human body growth and high commodity prices depending on the measurement indicators used to suit the nature of the research conducted in calves fattening production fields in Gogjali region- Nineveh  (2018). The basic source data of the study is obtained from sources on the ongoing ground- marketing questionnaire of three levels, the producer, the wholesaler, the retailer and two fields groups of caste random sample. The first group included (100) fields with imported calves class. The second included (51) fields with local calves class. Whereas, according to the production and marketing costs indicator, the average of marketing efficiency (ME1 ) of marketed meat in both groups of claves fattening fields amounted (92.47, 93.39%) respectively for a kilogram which is a sign of high production costs and, according to the marketing margins indicator, the average of marketing efficiency (ME2 ) of marketed meat in both groups of claves fattening fields amounted (86.89,79.13 %) for per kg which is a sign of high marketing margins. Thus the study concluded a high value of marketing efficiency using the first scale with the fattening period time for both groups while marketing efficiency by using the second scale was characterized by the gradual decline in the imported fattening fields and a gradual rise in the local fattening fields.  The study recommends supporting production inputs (fodder, treatment), unifying markets and limiting the    importation of red meat importation  in order to obtain a good production and currency policy by which the production costs could be reduced to the minimum .